Functional differences in the hamstring muscles during sprinting - Higashihara, A.; Ono, T.; Nagano, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to demonstrate the respective activation of the biceps femoris (BF), semitendinosus (ST), and semimembranosus (SM) muscles during overground sprinting. Lower extremity kinematics and the electromyographic (EMG) activities of the BF, ST, and SM muscles were recorded for 13 male sprinters performing overground sprinting at maximum effort. Mean normalized EMG activity was calculated in the early stance, late stance, middle swing, and late swing phases. The peak activation time during the stance and latter half of the swing phases was also calculated. Significantly different characteristics for EMG activation and different occurrences of peak activation of the BF, ST, and SM were found within the gait cycle, indicating that the activation demand of each hamstring muscle differs during sprinting.